TEACHER COMPETENCY ON LEARNING AL-QURAN IN RAUDHATUL ATHFAL AT MEDAN - Halimah Sa'diyah; Saiful Akhyar Lubis; Fachruddin Azmi (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to determine the activities of the Ministry of Religious Affairs Office of Medan City in improving teacher competence in teaching Al-Qur’an, planning the learning of the teacher Raudhatul Athfal in teaching Al-Qur’an, the learning method that the teacher does in teaching Al-Qur’an, the obstacles faced by the teacher in teaching Al-Qur’an, and knowing the efforts conducted by the teacher in overcoming obstacles in teaching Al-Qur’an at Raudhatul Athfal in Medan City. Data collection techniques used were interviews, observation, documentation studies. Data management consists of data reduction, data display / data presentation, data analysis, techniques to ensure the validity of research results. The results of the study revealed that the activities of the Ministry of Religion of Medan City to improve the competence of teachers in teaching the Koran at Raudhatul Athfal Medan City are programs to improve teacher education qualifications, integrated competency-based training programs, education supervision programs and teacher empowerment programs through teacher learning planning Raudhatul Athfal in teaching The Koran at the Raudhatul Athfal City of Medan is a plan for organizing or organizing learning materials that will be given / taught to students consisting of plans for the preparation of the Semester Program (PROMES), Weekly Learning Implementation Plans (RPPM), Daily Learning Implementation Plans (RPPH), and Standard Operating Procedure (SOP)